Determination of Total Xanthone Content in the Preparation of Mangosteen Pericarp Capsules (garcinia mangostana l.) Available on the Market using UV-Visible Spectrophotometry Method - Delladari Mayefis; Yandri Anugerah; Roslinda Rasyid (Majalah Obat Tradisional, 2019)
The skin of Mangosteen fruit (Garcinia mangostana L.) is widely used as traditional medicine, for it contains a lot of xanthone compounds. Today, there are many products from mangosteen pericarp extract being sold on the market, one of which is the preparation of mangosteen pericarp capsules. Determining the total xanthone content in the preparation of mangosteen pericarp capsules (Garcinia mangostana L.) circulating on the market needs to be done to calculate the levels of xanthone that are not included in the preparation label. The results of the analysis with UV-Visible Spectrophotometry obtains the maximum absorption wavelength at 243 nm and the linear regression equation of the calibration curve that is y=0,0568+0,0727x with a value of r=0,9999. Validation of the analysis method showed the results of intraday precision obtained % RSD 0,34%, 0,17%, and 0,16%, interday precision of 0,23%, 0,35%, and 0,16%. The accuracy obtained was mean % recovery 95,55%, limit of detection 0,35 μg/ml and limit of quantitation 1,15 μg/ml. The results of the determination of the total xanthone content in the mangosteen pericarp capsules were 100,8 μg/mg in sample A; 197 μg/mg in sample B; and 50,2 μg/mg in sample C.